(untitled) (Journal of Enam Medical College, 2019)
Background: Intestinal obstruction is a common surgical problem that surgeons face in clinical practice. Still intestinal obstruction is a major problem in medical college hospitals in Bangladesh. Causes of intestinal obstruction remain same as earlier. There is lack of statistical data in our country. So, this study will be helpful in various aspect of management of intestinal obstruction patients by providing data. Objective: To find out similarities between preoperative diagnosis with actual peroperative findings of intestinal obstruction. Materials and Methods: This cross-sectional study was conducted from April 2013 to April 2014 at Enam Medical College Hospital and Dhaka Medical College Hospital. Two hundred patients were selected by purposive sampling of diagnosed cases of intestinal obstruction. Results: Among the subjects male were 124 (62%) and female were 76 (38%). Mean age was 34.56 ± 9.13 years. The maximum respondents were from 21–30 years age group (54%) followed by 31–40 years (18%) age group. Chronic intestinal obstruction was present in 53% cases and acute intestinal obstruction in 47% cases. The clinical profile showed that all patients had abdominal pain followed by vomiting (78%). The preoperative diagnosis of intestinal obstruction was neoplastic obstruction (24%) followed by obstructed hernia (22.5%). The highest similarities (100%) were observed in case of volvulus and ileosigmoid knotting. Obstructed hernia had the highest accuracy (97.7%) followed by neoplastic obstruction (91.66%). Maximum patients (13.5%) suffered from wound infection followed by burst abdomen (3%). Conclusion: The preoperative diagnoses are very much similar to peroperative findings. The clinical parameters and other mandatory diagnostic tools commonly used in tertiary level hospitals in our country showed diagnostic accuracy in diagnosis of intestinal obstruction. J Enam Med Col 2019; 9(3): 155-159